Analisis Penyerapan Aspirasi Masyarakat Melalui Kegiatan Kunjungan Kerja: Studi pada Masyarakat Provinsi Sumatera Utara (SUMUT 1) - Susanto, Hendro; Ernungtyas, Niken Febrina; Prisanto, Guntur Freddy; Afriani, Anindita Lintangdesi (Universitas 17 Agustus 1945 Surabaya, 2021)
The working visit or recess of the DPR RI is carried out to realize the aspirations of the right people on target to achieve political goals. This activity is also inseparable from the things considering that it follows local government policies and the DPRD to be said to be a successful activity. The purpose of this study was to analyze the aspiration absorption strategy through recess activities. This research method uses a qualitative-descriptive approach with in-depth interviews with three informants, namely members of the Indonesian Parliament and representatives of the electoral district of North Sumatra 1. The study results state that the strategy for absorbing people's aspirations is carried out through various forms of aspiration by involving community groups. The main structure of a method for capturing aspirations is through face-to-face dialogue with communities. People's aspirations were complete when they had felt the benefits directly. Keywords: community aspirations, political communication, recess, communication strategy